Synapsis-dependent allelic complementation at the decapentaplegic gene complex in Drosophila melanogaster. - Gelbart, W M (1982)
Allelic complementation at the decapentaplegic gene complex (dpp: 2-4-0, cytogenetic location: polytene chromosome bands 22F1-3) of Drosophila melanogaster frequently occurs between site mutations. Two specific instances of allelic complementation are shown to be dependent upon normal somatic chromosome synapsis of homologous dpp genes. Numerous strains have been identified that bear lesions that disrupt allelic complementation when heterozygous with structurally normal chromosomes; each of these 57 strains contains a gross chromosomal rearrangement with a break on chromosome 2. The properties of the rearrangements carried by 50 of these strains are consonant with the idea that their effects are due to a disruption of somatic chromosome synapsis in the dpp region of chromosome arm 2L. In double heterozygotes of simple two-break rearrangements, allelic complementation is restored (presumably through the restoration of structural homozygosity). The types of rearrangements that disrupt complementation have properties very similar to those of rearrangements that disrupt the transvection effect at bithorax [Lewis, E. B. (1954) Am. Nat. 88, 225-239]. The existence of synapsis-dependent allelic complementation is a demonstration of the physiological importance of nuclear organization in gene expression.